PERKEMBANGAN PEMIKIRAN FILSAFAT DALAM JURISPRUDENSI ISLAM - Musyahid, Achmad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2010)
This article studies the development of philosophical thought in Islamic jurisprudence. This study aims at tracing the origin and transformation of philosophical thought in Islamic world, and the influence of philosophical thought in the development of Islamic social law. This article demonstrates that the philosophical thought in Islamic law finds its fundamental bases in the Qur’an and hadits. These fundamental bases have then been developed by Islamic scholars in the philosophy of Islamic law.